Blind-eye cannulation as a new method for ERCP training: Can we do more than merely teach? - Boškoski, Ivo; Webster, George; Tringali, Andrea; Familiari, Pietro; Perri, Vincenzo; Costamagna, Guido (Endoscopy International Open, 2020)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) requires extensive hands-on training. Currently in ERCP training there are two very important problems that need attention: lack of standardized commands for communication, and misunderstanding between the trainee and the trainer.Methods A method of “blind-eye” cannulation was developed with two paired trainees using the Boškoski-Costamagna ERCP Trainer. The trainee who was holding the duodenoscope was blind-folded and the other trainee gave instructions on what maneuvers were necessary to achieve cannulation, under the supervision of a trainer. Before starting cannulation, a standard list of commands was agreed by the operators.Results The blind-eye method of cannulation teaches the operator trainee to listen and the assistant trainee to teach. Trainees use standardized commands. During the training session the two trainees swapped roles.Conclusions Currently, we do not have proof that this type of training is useful, therefore, scientific studies are needed for confirmation. However, we believe that this ERCP model may provide an entirely safe means of improving communication and technical proficiency.